Table S2 from A Single-Cell Taxonomy Predicts Inflammatory Niche Remodeling to Drive Tissue Failure and Outcome in Human AML - Lanpeng Chen (16918293) (2025)
Table S2 Differentially expressed genes in the HSC (low-output) cluster 0 vs. (high-output) HSC/MPP clusters 1-4